Between arts and knowledge: bells that enhance the city of faith (Research, Society and Development, 2022)
This article presents a study on the life trajectory, knowledge and arts, of Getúlio Colares Pereira, a citizen who worked with love and dedication as a bell ringer at the Basilica of São Francisco das Chagas in Canindé-Ceará. We carried out this bibliographic research using books, articles and legal documents as sources. The objective of this work is to study the life story of Getúlio Colares Pereira, his teachings and the art developed in the tolling of the bell. We seek to identify the knowledge that this bell ringer provided, showing his achievements and his paths to reach the title of Living Treasure and later the degree of Master of Culture by the Federal University of Ceará (UFC). We conclude through this research that knowledge of the world combined with a lifetime of work can change the history of a human being. The culture and knowledge of this Master of Culture are increasingly being valued by scholars and researchers. The Master of Popular Culture Getúlio Colares Pereira, educated by example, for the love of what he did, for faith, for the joy with what he did, for the persistence in making share what he knows with those who let himself be captivated and, thus, his students learn by making the ringing of the bell a continuous culture for new generations.